Prime Control-IQD: a Platform for Software Quality Analytics - Arantes, Everton; Corrêa, Ana; Perreira, Pedro; Fernandes, Tania; Trevisan, João; Durelli, Vinicius; Eler, Marcelo; Endo, Andre (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2023: Anais do VIII Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2023)
During the software development process, a huge amount of data about what is happening is produced and stored. Such a fact is even amplified when distributed software development and several working teams are taken into account. From the operational to the strategic level, it is difficult to reason about the process and make informed and evidence-based decisions about the development process. This paper introduces Prime Control-Intelligent Quality Dashboard (IQD), a platform that supports software quality analytics; its main goal is to provide means for stakeholders to understand the status of software projects from a quality perspective and to support decision making processes. So far, we deployed Prime Control-IQD in ten clients, extracting data and presenting visually pieces of relevant information for several professionals and managers. It has replaced manual in-house initiatives and there has been a constant demand for new features and evolution.